Protective effects of rosmarinic acid against azoxymethane-induced colorectal cancer in rats - Ilhan, Nevin; Bektas, Ibrahim; Susam, Solmaz; Ozercan, Ibrahim H. (Wiley, 2022)
Colorectal cancer (CRC) incidence is increasing gradually and has been become one of the most common cancers worldwide. Hence, it is important to discover cheap, naturally occurring compounds to be effective in suppressing the devastating effect of colon-related tumors. Rosmarinic acid (RA), one of the compounds of plant origin, possesses attractive features for use as an agent for cancer prevention and treatment. This study investigated the ability of RA to prevent azoxymethane (AOM)-induced rat colon carcinogenesis by evaluating the effect of RA on tumor formation and circulatory oxidant-antioxidant status. Moreover, plasma levels of adiponectin (APN) monocyte chemoattractant protein-1 (MCP-1), interleukin-6 (IL-6) were detected by enzyme linked immunosorbent assay. The animals were divided into three groups: Control, AOM, and AOM + RA. Rats were fed a modified pellet diet (15.8% peanut oil was added to the standard diet) during the experimental period. Colon cancer was formed by applying 15 mg/kg AOM intraperitoneal once a week for 4 weeks in both the CRC group and AOM + RA group. Besides AOM, AOM + RA group received 5 mg/kg body weight RA orally every day during the study. The results showed that adenocarcinoma rates formed 87.5% of the AOM group. With treatment of RA, a reduction in the incidence of adenocarcinoma was observed in the AOM + RA group. The plasma MCP-1, IL-6, and TO levels were significantly higher, APN and TAS levels were significantly lower in the AOM group with respect to controls. In addition, there was a significant increase in TAS levels in the RA treatment group compared to the AOM group. These findings suggested that RA may be beneficial in preventing AOM-induced colon carcinogenesis formation.
Keywords: adiponectin; colorectal cancer; MCP-1; oxidative stress; rosmarinic acid